1973
DOI: 10.2134/agronj1973.00021962006500030019x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interrelationships among Seedling Vigor, Field Emergence, and Yield in Wheat1

Abstract: To evaluate various seed quality criteria, 86 samples of spring wheat (Triticum aestivum L. ‘Manitou’), obtained from farmers in 1969, were grown in the same year with and without Panogen 15 seed treatment in replicated field trials at three locations in Saskatchewan. Untreated seed samples were grown again in 1970 at one of the locations. Determinations were made in the laboratory of various seed and seedling characteristics supposedly related to seedling vigor. Grain yield was increased significantly due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…However, field performance and germination as determined by a standard germination test, were not related. These observations support others (DasGupta and Austenson, 1973b;Sonntag et al, 1988) who have concluded that standard germination is inadequate for describing the true potential of wheat seed, particularly where plants may be subjected to stress at early developmental stages. Taken alone, the use of certified seed with a high germination percentage does not ensure a high degree of wheat tolerance to trifluralin residues.…”
Section: Discussionsupporting
confidence: 86%
“…However, field performance and germination as determined by a standard germination test, were not related. These observations support others (DasGupta and Austenson, 1973b;Sonntag et al, 1988) who have concluded that standard germination is inadequate for describing the true potential of wheat seed, particularly where plants may be subjected to stress at early developmental stages. Taken alone, the use of certified seed with a high germination percentage does not ensure a high degree of wheat tolerance to trifluralin residues.…”
Section: Discussionsupporting
confidence: 86%
“…The dry matter production of the seedling is the ultimate manifestation of physiological vigor (Heydecker, 1973). Seedling vigor is usually characterized by weight of the seedlings after a period of growth (Qualls and Cooper, 1968 and Dasgupta and Austenson, 1973). In the present study ,maximum vigor index was observed at cold storage.…”
Section: Impact Factor (Jcc): 59857 Naas Rating: 413supporting
confidence: 52%
“…These may measure seedling growth) (de Tempe 1963;Woodstock & Fesley 1965;Dasgupta & Austenson 1973;Perry 1977) or the response to moistures and temperature stresses (Matthews & Collins 1973;Stormonth & Doling 1979).…”
Section: Introductionmentioning
confidence: 99%